Quantification of Apoptosis and Necrosis by Flow Cytometry - Ormerod, Michael G.; Sun, Xiao-Ming; Brown, David; Snowden, Roger T.; Cohen, Gerald M. (Acta oncologica, 1993)
Apoptosis and necrosis are two important mechanisms of cell death. Several methods have recently been described for quantifying apoptotic cells by flow cytometry. We report a novel method for the quantification and separation of viable normal and apoptotic cells. We have applied this method both to immature rat thymocytes treated with a variety of agents and to a murine haemopoetic cell line after withdrawal of a growth factor. The cells were incubated with two dyes which give fluorescent complexes when bound to DNA, the bis-benzimidazole, Hoechst 33342, and propidium iodide. Three populations were identified and characterized. On excitation with UV radiation, dead cells fluoresced red due to the uptake of propidium iodide whereas apoptotic cells fluoresced bright blue; normal cells showed low blue, low red fluorescence. In this paper, we demonstrate how this method may be used to help to distinguish between cell death by apoptosis and necrosis.